Hysteria, notes on diagnosis in Brazil (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: The history of psychiatry in Brazil is mixed with the history of the institutions that took care of the alienated in the country, which date from the early twentieth century in the context of the nation's modernization and has subtle and explicit relations with the national morals of that age. The rate of women hospitalised by hysteria until 1920 at the main institution that separated and treated the insane, Rio de Janeiro's Hospital Nacional dos Alienados, was huge, and what characterised the disease was more linked to immoral behaviours than to organic illnesses. This experience of hysteria in Brazil is the subject of this article and its relations with the European conception guide still current reflections.Keywords: Hysteria. History of Psychiatry. Diagnosis. Women.